Spectrophotometric Estimation of Venlafaxine Hydrochloride - Singh Rathore, Garvendra; K. Basniwal, Pawan; Suthar, Manish; N. Gupta, Roop. (Asian Journal of Chemistry, 2010)
Two rapid, simple, precise and economical methods viz., linear regression equation and standard absorptivity were developed and validated for estimation of venlafaxine hydrochloride in capsule dosage form. The estimation of venlafaxine hydrochloride was carried out at 274 nm. Beer-Lamberts law was obeyed in the concentration range of 50-250 μg/mL and standard absorptivity A (1 %, 1 cm) was found to be 38.794 dl g-1 cm-1. The molar extinction coefficient (ε) for the drug was found to be 1214.267 mol-1 cm-1. Both methods were validated for linearity, accuracy, precision and robustness. The numerical value for all validation parameters lies within the acceptable limits.